Selected indicators of the range and use of printed resources in Polish academic libraries - Górny, Mirosław; Jazdon, Artur; Nowak, Piotr (My University, 1999)
Reports the results of a survey rating the amount and degree of the utilisation of printed materials in Polish academic libraries. The results which are presented by type (for example chemical, biological, technical libraries etc.) as well as by function (research libraries and libraries of educational institutions), concern the number of materials, including both books and periodicals. The authors include the amount of material in English as well as in other foreign languages. Figures illustrating the annual increase of these materials are also included. In addition, the article offers data which cover a number of * issues, including the range of materials which were ordered at the request of users, the time of cataloguing, the number of loans, the number of unfilled orders, the extent of the utilisation of the collections, the number of interiibrary loans, as well as the relegation of outdated materials. Finally, the survey reveals information on the number of libraries which research into user needs, the number of libraries which are open on Saturdays and Sundays, and the number of libraries which provide special services such as weekend loans.